Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/biot.201400862
|View full text |Cite
|
Sign up to set email alerts
|

Systematic microcarrier screening and agitated culture conditions improves human mesenchymal stem cell yield in bioreactors

Abstract: Production of human mesenchymal stem cells for allogeneic cell therapies requires scalable, cost‐effective manufacturing processes. Microcarriers enable the culture of anchorage‐dependent cells in stirred‐tank bioreactors. However, no robust, transferable methodology for microcarrier selection exists, with studies providing little or no reason explaining why a microcarrier was employed. We systematically evaluated 13 microcarriers for human bone marrow‐derived MSC (hBM‐MSCs) expansion from three donors to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 42 publications
7
92
4
2
Order By: Relevance
“…A 100 mL BellCo spinner flasks (Bellco Glass Inc., Vineland, NJ), were used for all spinner flask experiments, with a 100 mL working volume and a vessel diameter (T) of 60 mM. For all microcarrier cultures, Plastic P102‐L microcarriers (Pall Life Sciences, Portsmouth, UK) were employed (Rafiq et al, ). The same inoculation concentrations and culture methods were employed as described in Rafiq et al () except where improvements to the process were made (discussed in the Results section).…”
Section: Methodsmentioning
confidence: 99%
“…A 100 mL BellCo spinner flasks (Bellco Glass Inc., Vineland, NJ), were used for all spinner flask experiments, with a 100 mL working volume and a vessel diameter (T) of 60 mM. For all microcarrier cultures, Plastic P102‐L microcarriers (Pall Life Sciences, Portsmouth, UK) were employed (Rafiq et al, ). The same inoculation concentrations and culture methods were employed as described in Rafiq et al () except where improvements to the process were made (discussed in the Results section).…”
Section: Methodsmentioning
confidence: 99%
“…A recent analysis of the experimental processes, cost efficiency, and robustness of adherent cell culture technologies suggested that multi‐layered 2D culture vessels and stirred tank bioreactors with microcarriers could potentially replace conventional 2D culture platforms . Several thorough comparative investigations also indicated that microcarrier‐based 3D cultures provide the most efficient method for the in vitro expansion culturing of adherent cells, not only due to the volume economy arising from the high surface/volume ratio, but also due to the effectiveness of handling large numbers of cultured cells . These considerations elevated plastic microcarriers as the optimal choice for the scale‐up culture of postnatal stem cells, such as hMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…However for many clinical indications, achieving lot sizes of several hundred billion to trillions of cells will be imperative for commercial success; utilizing high-density bioreactor manufacturing platforms, such as stirred-tank bioreactors in conjunction with microcarriers, is likely to be the only way to accomplish this [21][22][23][24][25].…”
Section: Existing Manufac-turing and Distribution Solutionsmentioning
confidence: 99%